Development and In vitro-In vivo Characterization of Chronomodulated Multi-Particulate Drug Delivery System of Terbutaline Sulphate for Treatment of Nocturnal Asthma by box–Behnken Statistical Design - Prabhjot Singh Bajwa, Jaya Sharma, Shailesh Sharma, Anurag Bhargava (Journal of Applied Pharmaceutical Science, 2017)
This article is retracted.
Keywords: Chronotherapeutic, Box-Behnken, nocturnal asthma,Terbutaline sulphate, multi-particulate drug delivery system, Carbopol 971P.